3q-15=9+5q

Simple and best practice solution for 3q-15=9+5q equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3q-15=9+5q equation:


Simplifying
3q + -15 = 9 + 5q

Reorder the terms:
-15 + 3q = 9 + 5q

Solving
-15 + 3q = 9 + 5q

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '-5q' to each side of the equation.
-15 + 3q + -5q = 9 + 5q + -5q

Combine like terms: 3q + -5q = -2q
-15 + -2q = 9 + 5q + -5q

Combine like terms: 5q + -5q = 0
-15 + -2q = 9 + 0
-15 + -2q = 9

Add '15' to each side of the equation.
-15 + 15 + -2q = 9 + 15

Combine like terms: -15 + 15 = 0
0 + -2q = 9 + 15
-2q = 9 + 15

Combine like terms: 9 + 15 = 24
-2q = 24

Divide each side by '-2'.
q = -12

Simplifying
q = -12

See similar equations:

| (X/7)=-4 | | f(-20)=0.25x+260 | | 12w-10w-2=14 | | Y=(1/2)^2-1/2-42 | | 5*sin(x)=3-cos(2x) | | -16u+11u+10=-20 | | 1.8n=0.5n-11.44 | | 3x+6=-111-10 | | -6.6r=-4.7r+13.3 | | 3.1(f-14)+6.7=12.9 | | 5y+12=92 | | 9x+3=(-9x-10) | | -12.3b-12.95-9.94=-7.71-11.2b | | 4(5x-7)=10x+3 | | -2.6h+10.9=-4.4h-14.84 | | (3-x)=4 | | -14.87-4.5f=-3f+13.93 | | 3x+[4(x-1)]=45 | | -5.8f-13.89=-4.3f+12.96 | | y=4a+4a | | 14h+10=11h-8h-12 | | 2-13y=-13-14y | | 13h-12h+1=20 | | 12n+24=60 | | k^2+15k-25=0 | | 19j+18=18j | | 2n-n=7 | | -p-9=7p-1 | | 3/4x7= | | 3x+x+x+3x=70.08 | | 8n-13=5n+8 | | 2u+10=-6+8u-8 |

Equations solver categories